The Effect of Price on the Purchase Decision of Lettuce (Lactuca Sativa. L) in Kabong Cahaya, Tomagoba Village, Tidore District, Tidore City, Islands, North Maluku Province - Toduho, Fitriana K.; Azizah HS, Nur; Radjaloa, Vhyda Hamidah Aulia (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aims to determine the effect of price on the decision to buy lettuce in Kabong Cahaya, Tomagoba Village, Tidore City, Islands, North Maluku Province. This research was carried out from August to October 2020. The consideration for the research location that the authors take is that the range of research locations is still reachable. This type of research is quantitative research, the object of research that the authors take is consumers in the Tomagoba Village. Data collection was carried out by distributing questionnaires to all lettuce consumers according to the research samples in the field. The data analysis used is simple regression analysis. The results showed that the price variable had a positive effect on the decision to buy lettuce. Thus if farmers set an affordable selling price, it will affect a large number of purchasing decisions for lettuce and can increase income and business continuity of Kabong Cahaya Tomagoba.